2013
DOI: 10.5935/abc.20130163
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of the Dante Pazzanese Risk Score in Non-ST-Segment Elevation Acute Coronary Syndrome

Abstract: BackgroundIn non-ST-segment elevation acute coronary syndrome (ACS), the likelihood of adverse events should be estimated. Guidelines recommend risk stratification models for that purpose. The Dante Pazzanese risk score (DANTE score) is a simple risk stratification model composed with the following variables: age increase (0 to 9 points); history of diabetes mellitus (2 points) or stroke (4 points); no use of angiotensin-converting-enzyme inhibitor (1 point); creatinine elevation (0 to 10 points); combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The sociodemographic profile of the sample was similar to other studies, revealing mainly an average age above 60 years old, a slight predominance of males and the presence of cardiovascular risk factors classically reported in the literature (4,(12)(13)(14) . Lower income favors diseases and complicates the recognition of the signs and symptoms of acute myocardial infarction (12) .…”
Section: Discussionsupporting
confidence: 82%
“…The sociodemographic profile of the sample was similar to other studies, revealing mainly an average age above 60 years old, a slight predominance of males and the presence of cardiovascular risk factors classically reported in the literature (4,(12)(13)(14) . Lower income favors diseases and complicates the recognition of the signs and symptoms of acute myocardial infarction (12) .…”
Section: Discussionsupporting
confidence: 82%
“…This is consistent with the findings of others. In our country, the previously cited study by Santos et al 14 found that a diabetes diagnosis was significantly associated to all-cause mortality or re-infarction in 30 days. AlFaleh et al 28 analyzed 6,362 patients from the Gulf Registry of Acute Coronary Events-2 (Gulf RACE-2), and found that a history of diabetes or new-onset hyperglycemia at admission was associated with higher in-hospital, 30 day, and one-year mortality rates.…”
Section: Discussionmentioning
confidence: 56%
“…In Brazil, the Acute Coronary Care Evaluation of Practice Registry (ACCEPT study), a multicenter post-ACS Brazilian study with 2,485 patients, found a 30-day mortality rate of 1.8%, 3.0%, and 3.4% in individuals with UA, NSTEMI, and STEMI, respectively 13 . A study of 1,027 patients with NSTEMI from a single cardiology referral center in the city of São Paulo 14 found that 5.3% of the participants died or had a new infarction within 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 derivation studies [7,11,20,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] with 56,560 UA/ NSTEMI patients and 18 validation cohorts [18,20,22,24,28,30,[32][33][34][35][36][46][47][48][49][50][51][52] with 56,673 patients were included. As in ACS studies, validation cohorts included more NSTEMI patients than derivation ones (Table 2), with rates of PTCA ranging from 26 to 48%.…”
Section: Ua/nstemimentioning
confidence: 99%